2017
DOI: 10.1007/s12144-017-9760-z
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Post-Learning Wakeful Rest on the Retention of Second Language Learning Material over the Long Term

Abstract: Evidence exists that a brief period of wakeful rest after learning supports memory retention, while interference after learning weakens memory retention. We tested this so-called resting effect for second language learning material. In two counterbalanced within-subject designs, participants were involved in two identical successive learning phases. In each phase, they learned one of two second language stories, immediately followed by a recall phase in the first language. The critical manipulation took place … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 41 publications
2
25
2
Order By: Relevance
“…‘Resting effects’ on memory retention were found in healthy elderly and younger adults as well as amnesic and Alzheimer's disease patients with different encoding material and post‐encoding interference tasks (Alber, Della Sala, & Dewar, ; Cowan, Beschin, & Della Sala, ; Craig, Dewar, Della Sala, & Wolbers, ; Della Sala, Cowan, Beschin, & Perini, ; Dewar, Alber, Butler, Cowan, & Della Sala, ; but see Martini, Riedlsperger, Maran, & Sachse, ; Varma et al ., for inconsistent findings). Neuroscientific evidence exists that during resting previously encoded information is replayed (Deuker et al ., ; Tambini, Ketz, & Davachi, ).…”
Section: Introductionmentioning
confidence: 99%
“…‘Resting effects’ on memory retention were found in healthy elderly and younger adults as well as amnesic and Alzheimer's disease patients with different encoding material and post‐encoding interference tasks (Alber, Della Sala, & Dewar, ; Cowan, Beschin, & Della Sala, ; Craig, Dewar, Della Sala, & Wolbers, ; Della Sala, Cowan, Beschin, & Perini, ; Dewar, Alber, Butler, Cowan, & Della Sala, ; but see Martini, Riedlsperger, Maran, & Sachse, ; Varma et al ., for inconsistent findings). Neuroscientific evidence exists that during resting previously encoded information is replayed (Deuker et al ., ; Tambini, Ketz, & Davachi, ).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Varma et al () found no differences in forgetting rates when researchers asked participants to wakefully rest after encoding, compared with participants who worked on a two‐back task or even on a cognitively more effortful three‐back task. Similarly, Martini, Riedlsperger, Maran, and Sachse () found no differences between wakeful resting and task‐related cognitive engagement when they asked participants to encode texts in their second language, independent of whether participants were involved in a verbal (reading a newspaper article) or visuospatial (finding errors in pictures) filler task after encoding (see also Fatania & Mercer, ; Martini, Zamarian, Sachse, Martini, & Delazer, ). These results suggest that under certain conditions, task‐related cognitive and sensory engagement compared with wakefully resting do not differ in their impact on memory.…”
Section: Discussionmentioning
confidence: 97%
“…Importantly, we are not the first group to report null effects in a variant of the wakeful rest paradigm. Indeed, recent failures to extend the effect have been reported for both free recall Wakeful Rest 38 and recognition tests of verbal target materials (28,29). One account of some of these failures is provided by Varma and colleagues (28).…”
Section: Failure To Extend the Wakeful Rest Effect To Abstract Shapesmentioning
confidence: 98%
“…In a separate account of null effects in a wakeful rest paradigm, Martini and colleagues (29) suggest that their particular encoding paradigm might have produced highly elaborated memory traces, since they gave participants unlimited time to study emotionally arousing narratives (i.e., crime and accident scenes), under unusual testing conditions (i.e., narratives were studied in participants' second language and tested in their first language). Consequently, memory for the passages might be particularly stable and less affected by intervening distractors, limiting the sensitivity of their comparison across conditions.…”
Section: Failure To Extend the Wakeful Rest Effect To Abstract Shapesmentioning
confidence: 99%
See 1 more Smart Citation